Impact of oral conditions on salivary biochemical parameters in individuals with substance use disorder: a cross-sectional study - Julia Arruda BATISTA; Bruno WAKAYAMA; Rayara Nogueira de FREITAS; Gabriela Alice FIAIS; Antonio Hernandes CHAVES-NETO; Tânia Adas SALIBA; Artênio José Isper GARBIN; Clea Adas Saliba GARBIN (Brazilian Oral Research)
Abstract This study aimed to investigate oral conditions and their impact on salivary biochemical parameters in institutionalized individuals with and without substance use disorder. This was an epidemiological, cross-sectional, and clinical study. It included two groups, institutionalized individuals with substance use disorder (SUD group) and without substance use disorder (control group), each consisting of 60 participants. Salivary samples were analyzed for various parameters, while oral conditions were assessed using the DMFT index, community periodontal index, clinical attachment loss index, and need for prosthesis. Statistical analysis included the Mann-Whitney U test, t-tests, and correlation analysis (p ≤ 0.050). The SUD group showed a higher need for dental prostheses (p < 0.001) and more pronounced dental erosion (p < 0.001). This group also exhibited elevated DMFT indices, with significant associations in sextants with calculus (p = 0.010), periodontal pockets (p < 0.001), and attachment loss of 12 mm or more (p = 0.036). Regarding salivary parameters, the SUD group had high cortisol levels and significant correlations between uric acid and bleeding sextants (p = 0.024), salivary amylase and decayed teeth (p = 0.002), cortisol and the DMFT index (p = 0.045), and cortisol and the absence of DMFT (p = 0.042). In conclusion, individuals in the SUD group exhibited worse oral conditions than did those in the control group, suggesting a relationship between drug addiction and increased cortisol, uric acid, and salivary amylase levels.